EVOLUTION OF AGRARIAN STRUCTURE AND RELATIONS IN JAMMU AND KASHMIR: LATE 19TH CENTURY TO EARLY 20TH CENTURY - Prince Raina (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research work presents a comprehensive study of the agrarian structure and relations in the region of Jammu and Kashmir from the late 19th century to the early 20th century. Through an analysis of historical documents, governmental records, and scholarly research, the paper examines the transformation of land ownership, tenancy patterns, and socio-economic dynamics within the agrarian sector during this pivotal period. By delving into the colonial policies, socio-economic conditions, and local power structures, this research sheds light on the intricate interplay of factors that shaped the agrarian landscape of Jammu and Kashmir. Furthermore, it discusses the implications of these historical developments for contemporary environmental and agricultural policies aimed at fostering sustainable practices and equitable land distribution in the region.